(untitled) - Fujihara, Ginjiro (Tokyo, 1936)
This book is not a pirce of scholarly work, but it is hoped that what a captain of Japanese industry has to say may be of interest to those who care to have a deeper insight into economic life of the Japanese nation.
Keywords: Industries,Công nghiệp; Japan,Nhật Bản